Maize cropping systems and response of common bean in succession subjected to nitrogen fertilization - de Souza, Stefany Silva [UNESP]; Júnior, Pedro Afonso Couto [UNESP]; Flôres, Jordana de Araujo [UNESP]; Mingotte, Fábio Luiz Checchio [UNESP]; Lemos, Leandro Borges [UNESP] (My University, 2019)
The common bean succession to intercropped crops in the no-tillage system is beneficial, especially in the search for sustainability. In addition to the straw production, the intercropping can supply nitrogen (N) to the common bean grown in succession, reducing the use of mineral fertilizer, which is pollutant and has a high cost. The present study aimed to evaluate the response to N fertilization of common bean in succession to maize cropping systems, as well as the viability of these systems in the no-tillage system. The experimental design was randomized blocks, in a split-plot arrangement, with four replicates. The plots consisted of the following systems: Maize as a single crop, maize intercropped with brachiaria and maize intercropped with crotalaria. The subplots were five N doses (0 kg ha-1, 50 kg ha-1, 100 kg ha-1, 150 kg ha-1and 200 kg ha-1), applied as topdressing fertilization in winter common bean, in succession to the maize cropping systems. For the maize cultivation systems, the grain yield and N amount and accumulation in the straw were evaluated. As for the common bean in succession, the grain yield and grain quality attributes were assessed. Although the three cropping systems were viable for maize grain yield, the intercropping of maize with crotalaria led to a higher N accumulation in the straw and a larger quantity of straw dry mass. The increase of the N doses promoted an increase in the grain yield of common bean grown in succession to intercropped maize. Maize intercropped with crotalaria resulted in grains with a higher size and, concerning the grain yield, an equivalent effect to that of a topdressing application of more than 200 kg ha-1of N was observed for the common bean in succession.
Sistemas de consórcio de milho e resposta de feijoeiro em sucessão submetido a adubação nitrogenada
Keywords: Crotalaria spectabilis; Nitrogen dynamics; Phaseolus vulgaris; Straw production; Urochloa ruziziensis